Labral tear is associated with increased risk of osteoarthritis – A cross-sectional study - Ayesha Mughal; Danilo Vukanic; Evelyn Patricia Murphy; Geoffery Crozier-Shaw; Anant Mahapatra (Journal of Orthopaedic Reports, 2023)
Introduction: The significant risk factor for hip OA is abnormal joint morphology. Labral tear occurs secondary to femoroacetabular impingment and decreases the ability of joint to maintain normal synovial fluid pressure. Labrum acts as a gasket and leads to uniform distribution of joint pressure. With tear, the synovial fluid leaks and joint lubrication is compromised leading to abnormal loading and early OA. Objective: To find association between labral tear and hip Osteoarthritis. Background: Hip Osteoarthritis is one of the most common and disabling conditions affecting people at elderly age. A significant risk factor associated with onset of Osteoarthritis is abnormal joint morphology. The Labrum provides tight suction seal, increasing joint stability and also distributes forces. This provides a “gasket” –type effect. In labral tears, the capacity of the hip joint to maintain synovial fluid is reduced. This decreases joint stability and causes abnormal distribution of femoroacetabular forces. As chondral damage and subchondral lesions are among features of hip Osteoarthritis, labral tears are closely related to the progression of hip OA. The pathophysiology of labral tears and their association with hip Osteoarthritis is not completely understood and warrants further study. Methods: Single institution retrospective cross-sectional analysis was done. From January 2021 to February 2021, data was collected retrospectively for all patients getting MRI hip done. Results: Total number of patients included was 73 and Hip Osteorthritis was found in 7 (9.5%) patients with labral tear and the association was found to be significant with p-value of 0.015. Conclusion: Mechanical symptoms such as clicking, hip pain and decreased range of motion are commonly associated with underlying labral tears and cartilage defects. The association of labral tear with arthritis is significant. Therefore, when patient presents with mechanical symptoms, MRI should be considered to assess the labrum and cartilage.